2023
DOI: 10.1101/2023.10.28.564539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the biology and chemistry of the mutualistic partnership betweenBacillus velezensisand the arbuscular mycorrhizal fungusRhizophagus irregularis

Adrien Anckaert,
Declerck Stéphane,
Laure-Anne Poussart
et al.

Abstract: Arbuscular mycorrhizal (AM) fungi (e.g. Rhizophagus irregularis) recruit specific bacterial species in their hyphosphere. However, the chemical interplay and the mutual benefit of this intricate partnership have not yet been investigated especially as it involves bacteria known as strong producers of antifungal compounds such as Bacillus velezensis. Here, we show that the soil dwelling B. velezensis migrates along the hyphal network of the AM fungus R. irregularis, forming biofilms and inducing metabolic fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
0
0
0
Order By: Relevance
“…However, most of the BFI-related biofilm research focused on mycorrhizal fungi, which inherently cooperate with bacteria. For example, intricate interaction between B. velenzesis and the arbuscular mycorrhizal fungi, Rhizophagus irregularis suggested that the biosynthesis of specific lipopeptides and antimicrobial compounds in B. velezensis is attenuated as a mechanism to ensure stable coexistence of these two microoorganisms [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the BFI-related biofilm research focused on mycorrhizal fungi, which inherently cooperate with bacteria. For example, intricate interaction between B. velenzesis and the arbuscular mycorrhizal fungi, Rhizophagus irregularis suggested that the biosynthesis of specific lipopeptides and antimicrobial compounds in B. velezensis is attenuated as a mechanism to ensure stable coexistence of these two microoorganisms [44].…”
Section: Discussionmentioning
confidence: 99%